A multi-level approach to e-HRM motives and consequences in an MNC: A Case Study X - Rentto, Olga (My University, 2014)
The advancements in technology are changing the way human resources (HR) are man-aged. While electronic human resource management (e-HRM) is becoming increasingly popular among multinational corporations (MNC), the MNC context in the field of e-HRM suffers from a fundamental lack of empirical evidence. Therefore the purpose of this study is to analyze the perceptions different stakeholders have on e-HRM which was being implemented in the case company during the time of research. Three research questions were formed to deliver understanding to this purpose. The first research question aimed to understand the motives behind the implementation of e-HRM, why e-HRM is implemented, and what goals is the company aiming to achieve with e-HRM. The second research question focuses on the possible impacts e-HRM has on its end users. The final research question is aimed to deliver understanding on what the strategic potential of e-HRM covers and how the strategic potential is realized and why that does not necessarily happen. This study was conducted by following a qualitative case study method as it is the most eligible method in terms of the objectives of this study. The empirical data was gathered through conducting semi-structured interviews and secondary data provided by the case company. The interviewees represented three groups; top management, HR professionals and line managers. The data was analyzed using the content analysis method. Main findings suggest that the implementation of e-HRM is a multilevel phenomenon in several senses. It might change everyone’s roles, but the impacts can also be divided into operational and strategic ones. If the strategic potential realize by utilizing the new data transparently e-HRM can help the company gain competitive advantage.
Keywords: e-HRM; Human Resource Management; Information Systems; Information System Implementation; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Henkilöstöjohtamisen maisteriohjelma|en=Master's Programme in Human Resource Managment|